Analisis Efisiensi Produksi dan Nilai Mata Rantai Pemasaran Sayur Buncis di Kabupaten Wonosobo (Studi Kasus Kecamatan Kalikajar) - Aprilia Dewi Novita; Sucihatiningsih Dian Wisika Prajanti (Journal of Economics and Business, 2020)
The aims of this research are 1.) To analyze the production efficiency of bean vegetable farming in Wonosobo Regency 2.) To analyze the value chain of bean vegetable marketing in Wonosobo Regency, especially in Kalikajar District. This research is descriptive quantitative. With the sampling technique using purposive sampling where the sample is taken based on certain considerations. Where the largest bean vegetable producing area is taken in Wonosobo Regency. The analytical tool used in this research is the Cobb-Douglass production function with a Stochastic Frontier approach and marketing margin analysis. To calculate the value of production efficiency using Frontier 4.1 Software. The results showed that all production factors had a positive effect on the production of green beans with an efficiency value of 0.998. The results show that it is not yet technically efficient. while on the marketing margin value, the most effective channel used is channel Zero, which is the percentage of profit for farmers is 100%, this is greater than channel 1 and channel 2 which have values ​​of 50% and 25%, respectively.